Executive dysfunctions in patients with low-grade gliomas in the supplementary motor area: a neuropsychological perspective - Bala, Aleksandra; Olejnik, Agnieszka; Rejner, Weronika; Gottman-Narożna, Antonina; Koczyk, Kacper; Dziedzic, Tomasz; Kunert, Przemysław (Frontiers in Human Neuroscience, 2025)
IntroductionThe supplementary motor area (SMA) is one of the more common locations where low-grade gliomas (LGG) are found. It is an area that, in addition to controlling movement, is also involved in a range of cognitive functions, including executive functions, but data on this topic is still scarce. The aim of this study was a comprehensive assessment of executive functions, as well as an evaluation of clinical variables that may influence the obtained results.Materials and methodsThe study included 23 patients with LGG tumors located in the SMA and a control group of 57 healthy individuals. They were all tested using a set of neuropsychological tests: the Stroop Test, the Verbal Fluency Test, the Tower of London Test, and the Wisconsin Card Sorting Test.ResultsThe conducted analyses revealed the presence of significant differences between groups in terms of selected indicators of each test. Furthermore, the results of individual TOL and WCST indicators showed significant correlations with the tumor volume. The comparison of patients with tumors in the left and right hemispheres revealed differences solely in WCST performance, with those having left SMA damage performing worse. There were also differences in the performance of the WCST test to the disadvantage of patients who had epileptic seizures compared to those who did not. Moreover, patients with oligodendrogliomas scored lower than those with astrocytomas on some of the WCST indices.ConclusionsPatients with LGG tumors in the supplementary motor area present a wide range of executive dysfunctions, including planning, reasoning, inhibition, switching, and cognitive flexibility. Both the volume and type of tumor, the hemisphere in which it is located and the occurrence of epileptic seizures may be related to the results. Future studies with larger cohorts are needed to confirm these findings.